Review of STI and HIV epidemiological data from 1990 to 2001 in urban Burkina Faso: implications for STI and HIV control. Issue 2 (30th March 2004) - Nagot, N; Meda, N; Ouangre, A; Ouedraogo, A; Yaro, S; Sombie, I; Defer, M C; Barennes, H; Van de Perre, P
Abstract : Objectives: To better understand the sexually transmitted infection (STI)/HIV dynamics in an urban west African setting in order to adapt STI/HIV control efforts accordingly. Methods: Review of STI and HIV epidemiological studies performed over the past decade in Bobo-Dioulasso, the second city of Burkina Faso. Trends in STI prevalence among commercial sex workers and the general population were assessed over time through studies that used the same recruitment and laboratory diagnostic procedures. Variations in aetiologies of vaginal discharge, urethral discharge, and genital ulcers were also evaluated among patients consulting for genital infection complaints. Antenatal clinic based surveys provided data to assess HIV trend among the general population. Results: We observed an important decline of classic bacterial STI such as syphilis, Neisseria gonorrhoea, Chlamydia trachomatis, and Haemophilus ducrey infections in all study groups. Trichomoniasis also declined but to a lesser extent. HIV infection followed the same trend at the same time, with a significant decline in the 15–19 year age group of pregnant women, suggesting a possible decrease of HIV incidence. Although no evidence of a causal relation can be drawn from this review, adoption of safer sex behaviour, introduction of the syndromic management (SM) approach, or higher antibiotic use may have contributed to these changes. Conclusions: Classic bacterial STI declined over the past decade in parallel with a stabilisation of HIV infection. Variations in syndromes aetiology and sexual behaviours should be monitored as part of STI surveillance in order to improve STI syndromic management algorithms and to adapt HIV/STI prevention efforts.